خصائص محاضر اللغة العربية الفعال من تصرف المحاضرين والطلبة في الجامعة الإسلامية العالم Characteristics of the effective Arabic language lecturer from the conduct of lecturers and students at the International Islamic University in Malaysia: A comparative study ية بماليزيا: دراسة مقارنة - Ali, Asem Shehadeh Saleh; Yousef, Norhamizan (المجلس الاعلى للغة العربية, 2019)
اللغة العربية تؤدي دورا مهما في كثير من البلدان في أوروبا وأمريكا نظرا إلى المكانة الاقتصادية التي تتمتع بها البلاد العربية حاليا، وأخذت جامعات عديدة في أنحاء العالم تشجع على تعلم اللغة العربية بوصفها لغة ثانية أو أجنبية، وأحياناً تفرض تعلم اللغة العربية على طلبة المدارس، كما هو في كثير من البلدان الإسلامية كماليزيا وإندونيسيا وبروناي وغيرها. تهدف هذه الدراسة إلى الكشف عن تصرف المحاضرين والمحاضرات الذين يعلمون اللغة العربية أثناء الدراسة في الجامعة الإسلامية العالمية بماليزيا مع الطلبة، والتعرف عن تصرف الطلبة حول خصائص محاضر اللغة العربية الفعال، والكشف عن الفروق ذات الدلالة الإحصائية بين تصرف المحاضرين والمحاضرات حول خصائص محاضر اللغة العربية الفعال. يعتمد هذا البحث على الدراسة الميدانية، ويستخدم المنهج الوصفي المقارن. وتوصلت الدراسة إلى عدد من النتائج، ومنها: أن فهم العربية لدى عينات الدراسة مهم في العبادة، لأن أذكار العبادة كلها بالعربية، وأن أهمية تعلم اللغة العربية ينبع في ربطها بفهم القرآن الكريم والسنة. النبوية، كذلك توصلت الدراسة إلى اعتراض المحاضرين والمحاضرات والطلبة على إجابة أسئلة الامتحان في الاستماع والقراءة باللغة الأم بدلا من العربية، واعتراض الطلبة على البدء التحدث باللغة العربية إلا بعد أن يكونوا مستعدين لذلك. Arabic has an important role to play in many countries in Europe and America due to the economic status of the Arab countries now. Many universities around the world are encouraged to learn Arabic as a second or foreign language, as in many Islamic countries such as Malaysia, Indonesia, Brunei and others. The purpose of this study is to expose the behavior of Male and female lecturers who teach Arabic during the to the students of Arabic at the International Islamic University Malaysia, to learn about the students 'behavior about the characteristics of the effective Arabic language and to detect the differences of statistical significance between the lecturers' . This research is based on the field study and uses the comparative descriptive approach. Result of the study, including: that the understanding of Arabic in the study samples is important in worship, because all the adoration of worship in Arabic, and that the importance of learning the Arabic language stems from linking them to understanding the Quran and Sunnah. The study also found that the lecturers, male students and female students objected to answering the exam questions in the mother tongue instead of Arabic. The students objected to starting to speak Arabic only after they were ready..